The behaviour of selected oral bacteria in single- and mixed-species biofilms - Wan Nordini Hasnor, W.I.; Razak, Fathilah Abdul; Yusoff, Mohd Md; Rahim, Zubaidah Haji Abdul (Asian Network for Scientific Information, 2008)
The objective of this study was to investigate and compare the adhering capacity of early colonizers of oral biofilm in a dynamic environment. The study was carried out by inoculating the early colonisers of oral biofilm (Streptococcus mitis, Streptococcus sanguinis and Actinomyces sp.) singly and in a mixture to the experimental pellicle in an artificial mouth (NAM) model for 24 h. This will form the respective 24 h single- and mixed-species biofilm. The bacterial population adhering to the experimental pellicle was determined and expressed as colony forming unit per ml (cfu mL-1). The adhered bacterial population was further confirmed using the Scanning Electron Microscope. It was found that S. mitis demonstrated maximum adherence (1153.33±132.46×104 cfu mL-1), followed by S. sanguinis (183.00±10.33×104 cfu mL-1) and by Actinomyces sp. (42.33±3.20×104 cfu mL-1). The adhering capacity of bacteria when present in a mixture of two-species was found to be reduced. However in a mixture of three species, it was found that the bacterial adherence was slightly increased. The difference in the adherence capacity of these bacteria to the experimental pellicle was found to be statistically significant (p<0.05). The results obtained in this study suggest that selected oral bacteria behave differently in a single- and mixed species biofilms. © 2008 Asian Network for Scientific Information.